Globalization, literacy levels and economic development - Alok Bhargava (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper estimated models for GDP growth rates, poverty levels, and inequality measures for the period 1990–2000 using data on 54 developing countries at five-yearly intervals. Issues of globalization were investigated by analysing the differential effects of the countries' exports and imports and by postulating trans-logarithmic models that allow for non-linear effects of literacy levels and measures of openness. The main findings were that literacy rates affected growth rates in a quadratic manner and countries with higher literacy were more likely to benefit from globalization. Second, the model for growth rates showed non-linear and differential effects of the export/GDP and import/GDP ratios. Third, the models indicated that population health indicators such as life expectancy were important predictors of GDP growth rates. Fourth, models for poverty measures showed that poverty was not directly affected by globalization indicators. Finally, the model for Gini coefficients indicated significant effects of `medium' and `high' skilled labour work force, with higher proportions of high-skilled labour implying greater inequality. – globalization ; economic development ; education ; endogeneity ; inequality ; poverty ; non-linearities ; trade
Keywords: C33; C5; I3; O11; O5; 330; Globalisierung; Entwicklung; Sozialprodukt; Armut; Einkommensverteilung; Analphabetismus; Entwicklungsländer